(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2021)
The Mutantur project is an experience that starts from understanding tourism as a socio-cultural activity that can act as a vehicle to regain access to the city from, by and for people on the street, guaranteeing the constitutional right to enjoy heritage and the knowledge of history to re-signify the present. Emerged in the Asamblea Popular Plaza Dorrego-San Telmo, it has become a device that collaborates in reducing the damage of highly vulnerable and stigmatized population. The UNDAV Tourism careers took part in 2018 with the purpose of strengthening the link within university and territory, promoting the construction of knowledge from a horizontal dialogic perspective with social actors and the demands of reality. The project assumes and recognizes the social mission of the public university, the central place of critical learning and the social practice necessary to transform reality.